Digital economy and education in China: globalisation and cyber sovereignty - M. Yu. Zakharov; A. V. Shishkova (Цифровая социология, 2024)
The article studies the socio-cultural specifics of digitalisation of public administration system, economy, and education of China. With the help of historical and philosophical, comparative, and hermeneutic methods alongside with the analysis of secondary sources and statistical information, the authors examine the socio- cultural features of Chinese strategy of digital breakthrough and the impact this strategy may have on the global world. The following problematic areas of digitalisation have been identified: transparency of public administration system that is relevant to the Zeitgeist and demanded by the population versus strict state control over various spheres of life; the global Internet versus cyber sovereignty; maintaining a balance between internationalisation and localisation of Chinese education. Several potential spheres of influence on the international community have been highlighted: world-class standardisation; demand for Chinese education (including education in the field of public administration) in the global market for educational services; development of artificial intelligence due to national peculiarities of China (a huge volume of domestic data, the possibility of mass implementation of developments, financial capabilities of the country). Special attention is given to the problem of cyber sovereignty. Within its framework, three main types of security that the Chinese information sphere concentrates on are analysed: computer, cognitive, information and psychological